Optimization Control in MG-16 DC Motor Using LQR and LQT Configurations - Nugraha, Anggara Trisna; Muhammad Bilhaq Ashlah; Rama Arya Sobhita; Dhadys Ayu Juli Anjhani (SAINSTECH NUSANTARA, 2025)
DC motors are widely used electronic components commonly found in everyday applications. Typically, when a load is applied, a DC motor tends to decelerate and fails to maintain a constant speed. To address this, motor speed can be controlled by adjusting the input voltage. However, to maintain consistent speed under varying loads, a control system is necessary. LQR works by adjusting the motor response to closely approach the desired setpoint, while minimizing both overshoot and undershoot within the system. On the other hand, LQT is a linear control strategy designed to ensure that the system output closely follows a time-varying reference or setpoint. When implemented, LQR yields a motor response that aligns with the target setpoint without any overshoot or undershoot. In contrast, if LQR is not applied, the motor response deviates significantly from the desired target and takes a longer time to settle. Meanwhile, the LQT method produces a quicker response reaching steady state in approximately ±0.5 seconds although it does introduce some overshoot and slight ripple in the signal. Despite these minor drawbacks, LQT is often favored over LQR for applications involving the MG-16B DC motor due to its superior speed in reaching the setpoint.